Genetic insights and emerging therapeutics in diabetic retinopathy: from molecular pathways to personalized medicine - Pei, Xiaoting; Huang, Duliurui; Li, Zhijie (Frontiers in Genetics, 2024)
Diabetic retinopathy (DR) is a major complication of diabetes worldwide, significantly causing vision loss and blindness in working-age adults, and imposing a substantial socioeconomic burden globally. This review examines the crucial role of genetic factors in the development of DR and highlights the shift toward personalized treatment approaches. Advances in genetic research have identified specific genes and variations involved in angiogenesis, inflammation, and oxidative stress that increase DR susceptibility. Understanding these genetic markers enables early identification of at-risk individuals and the creation of personalized treatment plans.Incorporating these genetic insights, healthcare providers can develop early intervention strategies and tailored treatment plans to improve patient outcomes and minimize side effects. This review emphasizes the transformative potential of integrating genetic information into clinical practice, marking a paradigm shift in DR management and advancing toward a more personalized and effective healthcare model.